Differential neurocognitive network perturbation in amnestic and aphasic Alzheimer disease. (18th February 2020) - Martersteck, Adam; Sridhar, Jaiashre; Rader, Benjamin; Coventry, Christina; Parrish, Todd; Mesulam, M.-Marsel; Rogalski, Emily
Abstract : Objective: To determine if Alzheimer disease (AD) is associated with aphasic rather than amnestic dementias in certain circumstances related in part to perturbations in different networks. Methods: Three groups were investigated: 14 participants suspected of having the neuropathology of AD based on clinically diagnosed amnestic dementia of the Alzheimer type (DAT), 26 individuals with primary progressive aphasia (PPA) with either a positive 18 F-florbetapir amyloid PET scan or confirmed AD at autopsy, and 26 neurologically intact controls. The groups were compared using rs-fMRI. Seeds included the left hemisphere inferior frontal gyrus (IFG) for the language network, the left hippocampus for the episodic memory network, and the left posterior cingulate for the default mode network (DMN). Results: Greater connectivity perturbations were found from the hippocampus for the DAT group and from the IFG for the PPA group. Furthermore, connectivity alterations in the PPA group were more asymmetric and favored the language-dominant left hemisphere. Loss of connectivity from the DMN seed was of a similar magnitude in the PPA and DAT groups. Conclusions: Despite the presumptive common underlying neuropathology of amyloid plaques and neurofibrillary tangles, the 2 groups displayed 2 different patterns of network perturbation, each concordant with the clinical presentation and the anatomy of neurodegeneration.